Educational difference in the prevalence of osteoporosis in postmenopausal women: a study in northern Iran - Maddah M; Sharami SH; Karandish M (BMC, 2011)
Abstract Background Osteoporosis is the most common metabolic bone disease in the world and it is rapidly increasing in Iran. In this study the relationship between educational levels and osteoporosis was investigated among Iranian postmenopausal women. Method and subjects Seven hundred and six women aged 50-75 years old were randomly recruited from urban (n = 440) and rural (n = 266) areas in Guilan. Osteoporosis was diagnosed by quantitative ultrasound technique and dual X-ray absorptiometry. Serum 25(OH) D3, body weight and height were measured in all subjects. Other data including age, educational level, menopause age, medications and history of illness were also collected. Results We found that the prevalence of osteoporosis was significantly greater among women with low educational level than women with high educational status (18.0% vs 3.8% P < 0.0001). However, women with low educational level had higher mean serum level of vitamin D than women with high educational level. Osteoporosis was significantly more prevalent among women living in rural areas than women living in urban areas (19.1% v.s 13.3%, P < 0.0001). Conclusion This study showed that educational level is associated with bone health in this population of postmenopausal women with significantly higher osteoporosis found in lower social groups. Therefore, we suggest that women with low social level should be carefully evaluated for signs of osteoporosis during routine physical examinations.